(untitled) (Bangladesh Journal of Zoology, 2012)
The present study deals with the estimation of fecundity and induced breeding of Mystus vittatus by using carp PG hormone. Four different doses were tested, viz. 6, 8, 10 and 12 mg/kg body weight for female and 3, 4, 5 and 6 mg/kg body weight for male. For each dose, three different sex ratios were maintained, viz. 1?: 1?, 2?: 1? and 3?: 2?. The hormone doses 8 mg/kg for female and 4 mg/kg for male provided the best result in the sex ratio 2?: 1?. This treatment combination revealed 80% fertilization and 56% hatching rates. Mean survival percentage of the spawns up to 10 days was 60%. DOI: http://dx.doi.org/10.3329/bjz.v39i2.10587 Bangladesh J. Zool. 39(2): 205-212, 2011